Unsubmissive Education towards Single Thought: Who Watches You? - Hernández Navarro, Carlos Estéban (2018)
In this paper, based on the novel written by George Orwell titled 1984 published in 1948, certain aspects will be analyzed that, when considered in the pedagogical context, could allow the outline of some criteria that contribute to the understanding of the need, in our present time, to propose an educational practice for life, as a political conscience. The objective of supporting human emancipation is pursued, in the fight against a violent system that is reproduced from the educational institutions, which is, due to its actions and selection of techniques, repressive and oppressive.